A case of Human Bone Chalcolithic Technology from the Perdigões site (Alentejo, Portugal) - Cunha, C. (2019)
A human femur diaphysis in the form of a burin was excavated from a secondary burial context containing osteological remains and industry in the Archaeological Complex of Perdigões (Portugal). The majority of these evidences are thermo-altered and highly fragmented. Radiocarbon dates for this context place it in the middle 3rd millennium BC. Typological analyses indicate that the human femur fragment is a burin, and use-wear comparisons suggest that it was used to drill hide.